CEO Cash Pay and Firm Performance in China under the Reformation of State-Owned Enterprise - Lu, Jiaqi (2020)
The agency problem between managers and owners has been the subject of widespread academic contestation for many years. Within the research areas of European and American markets, scholars have concluded that a positive, causal relationship exists between pay and performance evaluation; thus, this indicates that equity incentives are well developed and theoretically validated. With regards to China – a country whereby governmental organisations have a controlling position and pay incentives are underdeveloped – the question arises as to whether the relationship between Chief Executive Officer (CEO) pay and corporate performance equally justifies the effectiveness of pay incentives in helping to alleviate the aforementioned principle-agent issue.